(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
The shadow of erotism covers the act of all the characters in Inés Arredondo’s narrative: passion changes into a initiative route, in a run that the protagonists have to finish in order the get their conscience, trap of memory and brilliance of an apparent happiness in conflict with the reality. In “Sombra entre sombras” reality and fiction get together so as to form the tragic and erotic light of power.